Localização sonora com uma matriz de três microfones em um plano dimensional - Vieira, Arturo Veigel (2021)
Sound localization aids in the implementation of computational tools and provides applications in the areas of monitoring, security, virtual meetings, among others. It can be defined as the ability to identify the place of origin of the sound. This work presents a sound localization project carried out at the Universidade Tecnológica Federal do Paraná – Câmpus Curitiba, for analysis and an experimental observation of the use of cross-correlation techniques between signals for TDOA localization. The project was carried out through the processing of artificial signals emitted by a sound source located in four different positions, captured by a matrix of three microphones and computed using Audacity and MATLAB® softwares, to compare simulated and real results. Although it was not possible to carry out the assertive verification in all the scenarios experienced, it was obtained, within the error margins found, an outcome that could satisfy the applicability of the study developed according to the equipment available for such realization.